2011
DOI: 10.1007/s00586-011-1855-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid progression of spinal epidural lipomatosis

Abstract: Spinal epidural lipomatosis (SEL) is a rare but well-recognized condition. In general, the onset of its symptoms is insidious and the disease progresses slowly. We report two cases of rapid progression of SEL with no history of steroid intake in non-obese individuals after epidural steroid injection. These SEL patients developed neurologic symptoms after less than 5 months; these symptoms were confirmed to be due to SEL by serial MR images. After the debulking of the epidural fat, their symptoms improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 18 publications
(19 reference statements)
2
55
0
2
Order By: Relevance
“…However, there is a theoretical risk of worsening SEL with this procedure. Six cases of symptomatic lumbosacral SEL following epidural injection in patients with minimal to no prior SEL on imaging have been reported [39,[44][45][46][47]. McCullen et al describe the development of symptomatic SEL in a patient after 8 epidural steroid injections within two years, including 5 within 3 months for lumbosacral radiculitis.…”
Section: Discussionmentioning
confidence: 93%
“…However, there is a theoretical risk of worsening SEL with this procedure. Six cases of symptomatic lumbosacral SEL following epidural injection in patients with minimal to no prior SEL on imaging have been reported [39,[44][45][46][47]. McCullen et al describe the development of symptomatic SEL in a patient after 8 epidural steroid injections within two years, including 5 within 3 months for lumbosacral radiculitis.…”
Section: Discussionmentioning
confidence: 93%
“…Roy-Camille et al first reported SEL following a lumbar epidural steroid injection [41]. Additional patients have been described in the literature including Choi et al who described two with SEL caused by epidural steroid injection [36,37,44]. Few patient reports describe acute neurological deterioration in the setting of oral steroid administration.…”
Section: Discussionmentioning
confidence: 90%
“…Bowel and bladder incontinence are rare. The developed condition is likely to affect the thoracic and the lumbar spinal regions in equal proportions [7].…”
Section: Discussionmentioning
confidence: 99%
“…MRI typically shows a polygonal spiculated Y shaped or stellar morphological deformation of the dural sac in association with epidural fat overgrowth. It is thought that these characteristic spiculations correspond to the dural insertions of the meningo-vertebral ligaments while the depressions correspond to the accumulated epidural fat [7]. This configuration of deformed fat overgrowth could potentially cause spinal canal and/or trans-foraminal narrowing.…”
Section: Discussionmentioning
confidence: 99%